A potassium borate carbonate second-order nonlinear optical crystal material and its preparation and application
By introducing linear [BO2]-groups into potassium boric acid carbonate, the synthesis of new second-order nonlinear optical crystal materials of potassium boric acid carbonate has been solved, and the existing materials have been solved in terms of deep ultraviolet transmission, frequency multiplication response and optical performance are achieved, and efficient laser frequency conversion and broad photoelectric application prospects are achieved.
Patent Information
- Application Number
- CN202410502324.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-04-25
AI Technical Summary
There is still room for improvement in performance and application of existing deep ultraviolet-transmissive nonlinear optical crystal materials, especially the requirements for frequency multiplication response, birefringence and UV cut-off edges have not been fully met.
By introducing linear [BO2]-groups, a new second-order nonlinear optical crystal material of potassium boric acid carbonate is synthesized. The chemical formula is K9[B4O5(OH)4]3(CO3)(BO2)·7H2O, which belongs to the hexagonal crystal system and is prepared by solution evaporation method.
The crystal material exhibits strong powder frequency multiplication response, moderate birefringence and short UV cut-off edges, and can output strong 532nm green light under 1064nm laser irradiation, achieve phase matching, and have high optical transmittance in the UV-visible range.
Smart Images

Figure CN118186580B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonlinear optical crystal materials and relates to a potassium borate carbonate second-order nonlinear optical crystal material and a preparation method and application thereof.
[0002] Material research background
[0003] Nonlinear optical (NLO) crystals have a wide range of applications in optoelectronic fields such as lithography, spectral analysis, precision manufacturing, and environmental monitoring. Creating new UV (especially deep UV) NLO materials is the focus and difficulty of current research. BO and CO bonds are conducive to the transmission of UV light, so an effective strategy for developing new (deep) UV-transmitting NLO materials is to introduce π-conjugated structural units containing BO and CO bonds (e.g. [BO3] 3- ,[CO3] 2- ), such as the commercialized LiB3O5(LBO), CsB3O5(CBO), CsLiB6O 10 (CLBO), β-BaB2O4 (BBO) and KBe2BO3F2 (KBBF) crystals. Although the above crystals have excellent comprehensive properties, with the development of society and the continuous expansion of application fields, the requirements for NLO crystal materials are getting higher and higher. It is extremely urgent to develop high-performance deep ultraviolet transmittance NLO crystal materials. Summary of the invention
[0004] The purpose of the present invention is to provide a potassium borate carbonate deep ultraviolet transmittance second-order nonlinear optical crystal material and its preparation and application, the linear [BO2] - The groups greatly enhance the linear and nonlinear optical properties of potassium borate carbonate. Potassium borate carbonate exhibits a strong powder double frequency response (1×KDP), a moderate birefringence (0.031@546nm) and a short UV cutoff edge (less than 190nm).
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the technical solutions of the present invention provides a deep ultraviolet-transmitting potassium borate carbonate second-order nonlinear optical crystal material, characterized in that the chemical formula of the crystal material is K9[B4O5(OH)4]3(CO3)(BO2)·7H2O, the molecular weight is 1154.64, belongs to the hexagonal system, and its space group is The unit cell parameters are α=β=90°,γ=120°,Z=6,the unit cell volume is
[0007] Furthermore, the chemical formula of the crystalline material is K9[B4O5(OH)4]3(CO3)(BO2)·7H2O, which belongs to the hexagonal system and has a space group of The unit cell parameters are α=β=90°,γ=120°,Z=6. Further preferably, the unit cell parameters are α=β=90°,γ=120°,Z=6. Most preferably, the unit cell parameters are α=β=90°, γ=120°, Z=6.
[0008] The crystal structure of potassium carbonate borate of the present invention is as follows Figure 1 As shown. Two [BO4] 5- Tetrahedron and two [BO3] 3- The triangles are formed by sharing oxygen vertices [B4O5(OH)4] 2- Group. Each [B4O5(OH)4] 2- The group is hydrogen bonded to four adjacent [B4O5(OH)4] 2- The groups are connected to form a two-dimensional Layer. K + Atoms and [CO3] 2- The distribution of groups in Interlayer. Linear [BO2] - The groups are distributed in the pores of the three-dimensional structure in a consistent arrangement direction, resulting in a large second-order nonlinear optical effect in the crystal material. 2- Hydrogen bonding between the groups and H2O, The layers are stacked parallel to each other along the c-axis, ultimately forming a three-dimensional honeycomb-like structure.
[0009] The second technical solution of the present invention provides a method for preparing a potassium borate carbonate deep ultraviolet transmittance second-order nonlinear optical crystal material, which comprises mixing a K source, a B source, a C source and water and continuously stirring until a clear and transparent solution is obtained, and volatilizing at room temperature to obtain a colorless and transparent crystal, which is the target product.
[0010] Furthermore, the added amounts of K source, B source and C source satisfy: the molar ratio of K element, B element and C element is (2-40):(1-5):(1-20), preferably (1-20):(1-2.5):(1-10).
[0011] Furthermore, the volatilization temperature of the solution is 25 to 55° C., more preferably 30 to 35° C., and the volatilization time is not less than one week.
[0012] Further, the K source is potassium carbonate, potassium nitrate, potassium chloride, etc. Preferably, the K source is potassium carbonate.
[0013] Furthermore, the B source is boric acid or the like.
[0014] Furthermore, the C source is potassium carbonate or the like.
[0015] The third technical solution of the present invention provides a deep ultraviolet-transmitting potassium borate carbonate second-order nonlinear optical crystal material for use in laser frequency converters, optical parametric oscillators, optical parametric amplifiers and photoelectric rectifiers.
[0016] Furthermore, when the potassium borate carbonate second-order nonlinear optical crystal material is used in a laser frequency converter, it is used to output 532nm laser under 1064nm laser irradiation.
[0017] Specifically, K9[B4O5(OH)4]3(CO3)(BO2)·7H2O crystal is used as a nonlinear optical crystal material. It outputs a strong 532nm green light under 1064nm laser irradiation, and its powder frequency-doubled intensity is about 1 times that of KDP crystal, and phase matching can be achieved.
[0018] According to the strategy of super halogen substitution, [BO2] - The first example of [BO2] - The deep ultraviolet-transmitting nonlinear optical material K9[B4O5(OH)4]3(CO3)(BO2)·7H2O of the group has a linear [BO2] - The groups enhance the linear and nonlinear optical properties of the crystalline material. Potassium carbonate borate exhibits a strong double frequency response (1×KDP), a moderate birefringence (0.031@546nm) and a short ultraviolet cutoff edge (less than 190nm).
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] (1) The present application provides a new nonlinear optical crystal K9[B4O5(OH)4]3(CO3)(BO2)·7H2O. The crystal material has a large frequency doubling effect. Under 1064nm laser irradiation, its magnitude is about 1 times the frequency doubling intensity of the KDP crystal, and phase matching can be achieved. In addition, the crystal material has a high optical transmittance in the ultraviolet-visible light range of 190 to 800nm, and its ultraviolet absorption cutoff wavelength is less than 190nm. Therefore, the crystal material has broad application prospects in the field of nonlinear optics.
[0021] (2) The present application also provides a method for preparing the nonlinear optical crystal K9[B4O5(OH)4]3(CO3)(BO2)·7H2O, which uses a solution evaporation method to grow a colorless K9[B4O5(OH)4]3(CO3)(BO2)·7H2O crystal. The method is simple in process, mild in conditions, and can easily grow large single crystals with high optical quality and high purity.
[0022] (3) The potassium borate carbonate crystal material of the present invention can be applied to a laser frequency converter, and can be used to output a laser beam as a doubled frequency harmonic. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the crystal structure of potassium carbonate borate;
[0024] Figure 2 The X-ray diffraction pattern of sample 1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 1# is ground into powder;
[0025] Figure 3 is the UV-visible absorption spectrum of sample 1#;
[0026] Figure 4 is the infrared spectrum of sample 1#;
[0027] Figure 5 It is the solid state of sample 1# 11 B NMR spectrum;
[0028] Figure 6 This is the thermogravimetric analysis spectrum of sample 1#;
[0029] Figure 7 It is the second harmonic signal diagram of sample 1# and KDP sample with size ranging from 105 to 150 μm;
[0030] Figure 8 This is the second harmonic phase matching diagram of sample 1# in the 1064nm band. DETAILED DESCRIPTION
[0031] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0032] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0033] Embodiment 1:
[0034] Preparation of samples 1# to 8#
[0035] K source, B source, C source and water are mixed into a raw material in a certain proportion, placed in a polytetrafluoroethylene beaker and stirred continuously until a clear and transparent solution is obtained. Colorless and transparent K9[B4O5(OH)4]3(CO3)(BO2)·7H2O crystals can be obtained by slowly evaporating at room temperature.
[0036] The relationship between the type and ratio of raw materials in the initial mixture, the volatilization temperature, the volatilization time and the sample number is shown in Table 1.
[0037] Table 1 Correspondence between samples, raw materials and synthesis conditions
[0038]
[0039] Crystal structure analysis of samples 1# to 8#
[0040] The structure and phase analysis of samples 1# to 8# were carried out using single crystal X-ray diffraction and powder X-ray diffraction methods.
[0041] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-97 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.
[0042] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 10-70°, and the scanning step is 0.02°.
[0043] Among them, the single crystal X-ray diffraction results show that samples 1#~8# have the same chemical formula and crystal structure. The chemical formula is K9[B4O5(OH)4]3(CO3)(BO2)·7H2O, belonging to the hexagonal system, with a space group of P62c and unit cell parameters of α=β=90°, γ=120°, Z=6.
[0044] Take sample 1# as a typical example, its crystal structure data is α=β=90°,γ=120°,Z=6. Its crystal structure is as follows Figure 1 shown.
[0045] The powder X-ray diffraction test results show that in the XRD spectra of samples 1# to 8#, the peak positions of each sample are basically the same, but the peak intensities are slightly different.
[0046] Take sample 1# as a typical example. Figure 2 As shown, according to the crystal structure analyzed by single crystal X-ray diffraction, the fitted X-ray diffraction pattern is consistent with the pattern obtained by X-ray diffraction test after sample 1# is ground into powder, and the peak position and peak intensity are consistent, indicating that the obtained sample has high purity.
[0047] UV-Vis absorption spectrum test
[0048] The diffuse reflectance absorption spectrum test of sample 1# was conducted on a Cary 5000 UV-visible-near infrared spectrophotometer from Agilent Technologies, USA. Figure 3 As shown by Figure 3 It can be seen that the compound has no obvious absorption in the range of 190nm to 800nm. The compound has a wide optical transmission range and an optical band gap greater than 6.53eV.
[0049] Infrared spectrum test
[0050] The infrared spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 4 As shown, it is proved that the crystal material contains [BO2] - , [BO3] 3- , [BO4] 5- , [CO3] 2- Anionic groups and water molecules. Among them [BO2] - The characteristic peaks of anionic groups are at 1711 and 1626 cm -1 Place.
[0051] Solid State 11 B NMR
[0052] Solid State 11 B NMR test was carried out on Avance III HD 800MHz (18.8T) NMR spectrometer of Bruker Company, Germany. 11 The resonant frequency of B is 256.8MHz. MAS 11B NMR spectra were recorded in a 3.2 mm HXY CP / MAS probe using a single non-selective excitation pulse with a short pulse length (0.25 μs at a tilt of pi / 12) in order to obtain quantitative results under quadrupole nuclear nutation. For the MAS spectra, 12,000 scans were performed with a recycle delay time of 10 s and a spinning frequency of 22 kHz. Chemical shift reference values were obtained for 1 M H3BO3 solution. 11 B (δ = 19.6 ppm). The results are as follows Figure 5 As shown, it is proved that the crystal material contains [BO2] - , [BO3] 3- , [BO4] 5- Three anionic groups.
[0053] Thermogravimetric testing
[0054] The thermogravimetric test of sample 1# was conducted on a Netzsch STA409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. Figure 6 As shown by Figure 6 It can be seen that the thermal decomposition temperature of the compound is 61°C.
[0055] Frequency doubling test experiment and results
[0056] The frequency doubling test experiment of sample 1# is as follows: a laser with a wavelength of 1064nm generated by a Q-switched Nd:YAG solid laser is used as the fundamental frequency light to irradiate the tested crystal powder, a photomultiplier tube is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the control sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve. The particle size ranges are less than 26, 26-50, 50-74, 74-105, 105-150, 150-200, and 200-280μm. Observe the trend of the frequency doubling signal intensity changing with the particle size to determine whether phase matching can be achieved. Under the same test conditions, the second harmonic intensity generated by the sample and the KDP sample is compared to obtain the relative size of the sample frequency doubling effect.
[0057] The test results show that the compound potassium borate carbonate crystal has a large frequency doubling effect. Under 1064nm wavelength laser irradiation, the frequency doubling signal intensity is 1 times that of the control sample KDP crystal (such as Figure 7 ), phase matching can be achieved (such as Figure 8 ).
[0058] The embodiments described above are intended to facilitate ordinary technicians in this technical field to understand and use the invention, and are not intended to limit the present application in any form. Any changes or modifications made by any technician familiar with this profession using the technical content disclosed above without departing from the scope of the technical solution of the present application are equivalent to equivalent implementation cases and are within the scope of the technical solution.
Claims
1. A potassium borate carbonate second-order nonlinear optical crystal material, characterized in that: The chemical formula of the crystalline material is K9[B4O5(OH)4]3(CO3)(BO2)·7H2O, the molecular weight is 1154.64, and it belongs to the hexagonal system. Its space group is P 2 c , the unit cell parameters are a = b = 11.11~11.31 Å, c = 17.15~17.35 Å, α = β = 90°, γ = 120°, Z = 6, the unit cell volume is V = 1875.6~1885.6 Å 3 .
2. The potassium borate carbonate second-order nonlinear optical crystal material according to claim 1, characterized in that: The crystalline material contains isolated linear [BO2] − Group.
3. A method for preparing the potassium borate carbonate second-order nonlinear optical crystal material as claimed in claim 1 or 2, characterized in that: First, mix the K source, B source, C source and water, and stir continuously until a clear and transparent solution is obtained, and then evaporate at room temperature to obtain colorless and transparent block crystals, which are the target product; The addition amount of K source, B source and C source satisfies: the molar ratio of K element, B element and C element is (2~40): (1~5): (1~20); The evaporation temperature of the solution is 25~55℃, and the evaporation time is not less than one week.
4. The method for preparing a potassium borate carbonate second-order nonlinear optical crystal material according to claim 3, characterized in that: The K source is potassium carbonate, potassium nitrate or potassium chloride.
5. The method for preparing a potassium borate carbonate second-order nonlinear optical crystal material according to claim 3, characterized in that: The B source is boric acid.
6. The method for preparing a potassium borate carbonate second-order nonlinear optical crystal material according to claim 3, characterized in that: The C source is potassium carbonate.
7. Use of the potassium borate carbonate second-order nonlinear optical crystal material according to claim 1 or 2, characterized in that: This crystal material is used in laser frequency converters, optical parametric oscillators, optical parametric amplifiers and optoelectronic rectifiers.
8. The use of the potassium borate carbonate second-order nonlinear optical crystal material according to claim 7, characterized in that: When the potassium borate carbonate second-order nonlinear optical crystal material is used in a laser frequency converter, it is used to output 532 nm green light under 1064 nm laser irradiation.
Citation Information
Patent Citations
Crystalline material Pb2(BO3)(NO3) as well as preparation method and application thereof
CN104451880A
Fluoromolybdenum oxygen fluoriodate nonlinear optical crystal material and preparation and application thereof
CN113249788A